REKONSTRUKSI EVALUASI PENDIDIKAN MORAL MENUJU HARMONI SOSIAL - Ulil Hidayah (Nurul Jadid University, 2018)
Various efforts have been made by the government to achieve the expected educational objectives. Starting from the centralization policy that changed into decentralization and then democratization to curriculum changes that are considered able to improve the quality and quality of education in Indonesia as a whole. However, the reality of educational output that occurs today is still covered by increasingly complex problems. Of all the problems of education, social disharmonization is the most striking picture indicating that education fails to form a civilized human being. This article seeks to review the evaluation of moral education on the subjects of Islamic Education and Civic Education. Both of these subjects are considered the most responsible for the ethics of thinking and behaving of educated human beings. According to the curriculum applied today the plans and learning process has been running well, but need to be re-constructed in the evaluation of student learning outcomes. In the hope that the main judgment is not just from the cognitive domain as a complete learning in the classroom, but more than that it is a real and permanent affective and psychomotor assessment in the student until he grows in the midst of a harmonious social society.